Portugal : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Portugal's significant flow imbalances have largely been corrected in the wake of the sovereign debt crisis, with employment increasing, output expanding, and the current account balance posting surpluses for the first time in decades. The economy has expanded at close to 1 percent per year on average since early 2013, with growth driven largely by consumption. The near-term outlook is benefiting from the trifecta of record-low interest rates, a weakening euro, and low oil prices. Output is expected to increase by 1.6 percent in 2015 and by 1.5 percent in 2016, with outlook for inflation improving as well.